2020
DOI: 10.3389/fnut.2020.581679
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Support and Clinical Outcome of Severe and Critical Patients With COVID-19 Pneumonia

Abstract: Background: In 2020, a novel coronavirus has spread throughout the world. More than four hundred thousand people have died of SARS-CoV-2 pneumonia, most of which were severe and critical patients. No effective antiviral treatment has been verified thus far. Nutrition support has become one of the important treatments for severe and critical patients.Methods: In this retrospective study, 26 severe patients and 22 critical patients with laboratory confirmed COVID-19 were enrolled. We recorded the diet and nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Nevertheless, in their study, the level of energy intake was considerably beyond that delivered to the patients in the current study. In comparison with other studies on critically ill settings, in which protein and energy cutoffs were more than in the present study, these cutoff values were lower (22,23), which is consistent with a few of the same studies on patients with COVID-19. Thus, it is obvious that even negligible differences between these little intakes could significantly alter the hazard of mortality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, in their study, the level of energy intake was considerably beyond that delivered to the patients in the current study. In comparison with other studies on critically ill settings, in which protein and energy cutoffs were more than in the present study, these cutoff values were lower (22,23), which is consistent with a few of the same studies on patients with COVID-19. Thus, it is obvious that even negligible differences between these little intakes could significantly alter the hazard of mortality.…”
Section: Discussionsupporting
confidence: 93%
“…These values reached 67.8 and 81.5% target estimated requirements in the late acute phase. Additionally, Yue et al ( 23 ) reported the average of 15.3 kcal/kg/day for actual energy intake and 0.62 g/kg/day for actual protein intake in critically ill patients with COVID-19 for duration of 7 days. The results of our study are closely consistent with these mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…A small retrospective study conducted in severe and critically ill Covid-19 patients in China reported that permissive under feeding is feasible in critically ill Covid-19 patients. 25 Interestingly, the LEEP Covid study reported that measured REE in critically ill Covid-19 patients were at the range of 15-20 kcal/kgBW during the first week, therefore, our study result was in line with LEEP Covid study. 5 Bivariate analysis found that variables which significantly associated with energy target achievement of 20 kcal/kgBW were mNUTRIC score, the use of mechanical ventilator, lactate level and route of nutrition were.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, the lack of nutrition knowledge among Indonesian participants can likely be explained by differences in the institutional structures of the healthcare systems. Nutritional support is an integral part of COVID-19 treatment, especially in those who are critically ill [29]. Managing nutritional support in critically ill patients requires specific knowledge and skills to prevent poor clinical outcomes [30].…”
Section: Discussionmentioning
confidence: 99%